If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5i + -6x = (10y) * i + 10 Remove parenthesis around (10y) 5i + -6x = 10y * i + 10 Multiply y * i 5i + -6x = 10iy + 10 Reorder the terms: 5i + -6x = 10 + 10iy Solving 5i + -6x = 10 + 10iy Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-10iy' to each side of the equation. 5i + -10iy + -6x = 10 + 10iy + -10iy Combine like terms: 10iy + -10iy = 0 5i + -10iy + -6x = 10 + 0 5i + -10iy + -6x = 10 Add '6x' to each side of the equation. 5i + -10iy + -6x + 6x = 10 + 6x Combine like terms: -6x + 6x = 0 5i + -10iy + 0 = 10 + 6x 5i + -10iy = 10 + 6x Reorder the terms: -10 + 5i + -10iy + -6x = 10 + 6x + -10 + -6x Reorder the terms: -10 + 5i + -10iy + -6x = 10 + -10 + 6x + -6x Combine like terms: 10 + -10 = 0 -10 + 5i + -10iy + -6x = 0 + 6x + -6x -10 + 5i + -10iy + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 -10 + 5i + -10iy + -6x = 0 The solution to this equation could not be determined.
| 3mx=p+2n | | 12x-10-6x=10 | | 18s^2-48s-66=0 | | 10x+20y+8x-10y=48 | | 2i(7-i)= | | 9x+7y=-10 | | -3(k-18)+17=11 | | 5(x+3)+9=8x-3(x-3) | | 12n-5=4n+2 | | 6x+23=7 | | x-(2.5/100)x=408028750 | | 4x+2x+8=56 | | 4-2y-you=12 | | 9s^2+sforS=3 | | -113-3x=7x+37 | | 8u^2+8u+2=0 | | 9x-2x+49=28 | | x^2-8x-598=0 | | a^2+8a+26=5-2a | | 9(2r-5)-31/2(14r-8) | | 4(x+5)=9x+2-5x+18 | | -n/2=3 | | 3nl=5n-6z | | 6(a-4)+2=182 | | 1.5x+2.0y=572.5 | | 10+6x=3x+4 | | 2x-55=35+5x | | 5x-95=-4x+85 | | 6*7-10= | | 5r+10=4r-16 | | 30x^2+31x+5=0 | | -91+12x=28+5x |